Avaliação da qualidade dos parâmetros físico-químicos do óleo de tucumã (Astrocaryum aculeatum) na cadeia produtiva na Amazônia: uma revisão - Amazonas, Clícia de Souza (Brasil, 2021)
The Amazon rainforest is rich in biodiversity and has a diversity of plant species, among which the tucumã of the amazon has been highlighted. The present study about "The Evaluating the quality of tucumã (Astrocaryum aculeatum) oil physicochemical parameters in the production chain’s Amazon: a review”, has as objective to do a compilation of studies on the analysis physic chemical tucumã (Astrocaryum aculeatum) oil and its production chain in the amazon region. As a specific objective, it is to understand the degree of scientific knowledge of this Amazonian input disclosed in national and international scientific publications the searches were carried out in the following databases: Science Direct, Scielo, Periódicos CAPES, Biblioteca Digital Brasileira de Teses e Dissertações. The selection criteria for the works were focused on the publication of articles, dissertations, and theses about methods of extracting oil from the tucumã mesocarp and almond, as well as the analysis of the physicochemical parameters of this oil, such as: acidity index, peroxide index, saponification index, iodine index, moisture, and density. Another selection criterion was about how it occurs the tucumã oil production chain’s Amazon. According to the results obtained in the bibliographic surveys, it was observed that tucumã from Amazonas is a fruit present in the diet of the north region, where it adds economic value to the region with the commercialization of the fruit in natura and with the filling in sandwiches and other foods. There are two types of oils can be extracted, the mesocarp and the almond, such inputs are sources of raw material for industries in the cosmetic and food segments. It is a fruit with high nutritional value. So, studies on the quality of the oils are particularly important for them to be checked if the physical and chemical parameters are in accordance with the rules of the National Agency of Sanitary Surveillance of Brazil (ANVISA), as well as for the diversified application and uses of this oil. When extracted, they are applied in formulations of body moisturizers, lotions, soaps, as well asstudied for applications in biodiesel, softener textile, dental biofilm and alternative to palm oil substitute in foods. Howsoever, there was a scarcity of studies related to the oil of this fruit, which is so present and abundant in north region of Brazil, Tucumã from Pará (Astrocaryum vulgare) is the fruit with the highest number of publications. Given the economic importance of the Amazon tucumã (Astrocaryum aculeatum) for the local community, it is recommended that more studies be carried out on this fruit, aiming at the growth of publications and greater recognition of its potential.